Patent landscape of not-in-kind active cooling technologies between 1998 and 2017. (10th May 2021) - Renaldi, Renaldi; Miranda, Nicole D.; Khosla, Radhika; McCulloch, Malcolm D.
Abstract: The rise in global cooling demand will have significant impacts on our efforts to limit climate change and foster sustainable development. Minimising these impacts requires further development of active cooling technologies, starting with an examination of existing technologies and their characteristics. This paper provides an overview of active cooling technologies using a patent landscape based on patent application data over the past 20 years. In developing the patent landscape, we searched the Derwent Innovation patent database, which contains more than 90 million patent documents, using technology-specific keywords and patent classification codes. A careful assessment of the resulting patent dataset shows a range of important trends about the evolution of cooling in the last two decades. Specifically, we discuss annual cooling technology patent application trends, countries of application, and patent assignees. The results show that patenting activity in the field of active cooling has increased significantly since 2010, mainly driven by the rapid patenting trend in China. Patents of the incumbent technology have been dominated by established manufacturers from Japan and the United States. Not-in-kind cooling technologies with a high number of patent applications include thermoelectric, magnetocaloric, evaporative, pulse-tube, absorption, and adsorption cooling. The results from examining this global patent help in understanding and shaping the global development of active cooling technology by providing new information on the major supplier countries, the key manufacturers, and maturity levels of alternative cooling technologies. Graphical abstract: Image 1 Highlights: The study presents the global patent landscape of active cooling technologies. Top five countries: China, Japan, South Korea, United States, and Germany. Top assignees are dominated by East Asian manufacturers. Promising alternative cooling technologies include magnetic and absorption cooling.